Compartmental Endoscopic Surgical Anatomy of the Inferior Intraconal Orbital Space - Maxfield, Alice Z.; Brook, Christopher D.; Miyake, Marcel M.; Bleier, Benjamin S. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives This study aims to define the endoscopic anatomy of inferior intraconal space, in terms of its neurovascular structures and relationship to fixed anatomic landmarks.Design A cadaveric anatomical study was conducted.Setting This study was conducted at an academic cranial base center.Participants Cadaveric subjects have been investigated.Main Outcome Measures After dissection of the inferior intraconal space, the number and position of ophthalmic artery (OA) and oculomotor nerve (OMN) branches to the inferior rectus muscle (IRM) were quantified relative to the fixed landmark of the posterior maxillary wall. The point where the OMN branch to the inferior oblique muscle (IOM) crossed the lateral IRM margin was quantified.Results A total of 18 OA branches were identified with a mean ± standard deviation of 2.6 ± 0.53 branches. The mean distance of the OA branch insertion from the posterior maxillary wall was 7.11 ± 5.65 mm. The average number of OMN branches to the IRM was 1.63 ± 0.74 with a mean insertion distance of 1.88 ± 1.89 mm. The OMN branch to the IOM crossed the lateral IRM margin 5.38 ± 5.42 mm from the posterior maxillary wall.Conclusions This cadaveric study quantifies the variability of two critical neurovascular structures salient to endoscopic approaches to the inferior intraconal space, the OMN, and OA contributions to the IRM. Knowledge of the interrelationship between these structures is essential in safe technique for dissection.
Keywords: intraconal orbital anatomy; oculomotor nerve; ophthalmic artery; endoscopic approach